Guanidin – ein neu entdecktes Substrat nitrifizierender Mikroorganismen - Michael Pester (BIOspektrum, 2024)

Succession of Bacteria and Archaea Within the Soil Micro‐Food Web Shifts Soil Respiration Dynamics - Mandip Tamang; Johannes Sikorski; Miriam van Bommel; Marc Piecha; Tim Urich; Liliane Ruess; Katharina Huber; Meina Neumann‐Schaal; Michael Pester (Environmental Microbiology, 2024)
Bacterivorous nematodes are important grazers in the soil micro‐food web. Their trophic regulation shapes the composition and ecosystem services of the soil microbiome, but the underlying population dynamics of bacteria and archaea are poorly understood. We followed soil respiration and 221 dominant bacterial and archaeal 16S rRNA gene amplicon sequencing variants (ASVs) in response to top‐down control by a common bacterivorous soil nematode, Acrobeloides buetschlii , bottom‐up control by maize litter amendment and their combination over 32 days. Maize litter amendment significantly increased soil respiration, while A. buetschlii addition caused an earlier peak in soil respiration. Underlying bacterial and archaeal population dynamics separated into five major response types, differentiating in their temporal abundance maxima and minima. In‐depth analysis of these population dynamics identified a broad imprint of A. buetschlii grazing on dominant bacterial ( Acidobacteriota, Bacteroidota, Gemmatimonadota, Pseudomonadota ) and archaeal ( Nitrososphaerota ) ASVs. Combined bottom‐up control by maize litter and top‐down control by A. buetschlii grazing caused a succession of soil microbiota, driven by population changes first in the Bacteroidota , then in the Pseudomonadota and finally in the Acidobacteriota and Nitrososphaerota . Our results are an essential step forward in understanding trophic modulation of soil microbiota and its feedback on soil respiration.

Plant roots but not hydrology control microbiome composition and methane flux in temperate fen mesocosms - Marc Piecha; Juergen Kreyling; John Couwenberg; Michael Pester; Anke Guenther; Levke Henningsen; Micha Weil; Gerald Jurasinski; Gesche Blume-Werry; Tim Urich; Haitao Wang (Science of The Total Environment, 2024)

Umweltrelevanz Stickstoff-umwandelnder Archaea für saubere Seen - Michael Pester (BIOspektrum, 2023)

Journal Club - Yvonne Mast; Nadja Patenge; Michael Pester; Andreas Seiffert-Störiko; Volkmar Braun; Andreas Diepold; Johannes Sander; Maria Dell; Christoph Meier; Patrick Mester; Daniela Kruck; Felix Kreissl; et al. (BIOspektrum, 2022)

A single Thaumarchaeon drives nitrification in deep oligotrophic Lake Constance - Janina Herber; Franziska Klotz; Benjamin Frommeyer; Severin Weis; Dietmar Straile; Allison Kolar; Johannes Sikorski; Markus Egert; Michael Dannenmann; Michael Pester (Environmental Microbiology, 2020)
Summary Ammonia released during organic matter mineralization is converted during nitrification to nitrate. We followed spatiotemporal dynamics of the nitrifying microbial community in deep oligotrophic Lake Constance. Depth‐dependent decrease of total ammonium (0.01–0.84 μM) indicated the hypolimnion as the major place of nitrification with 15 N‐isotope dilution measurements indicating a threefold daily turnover of hypolimnetic total ammonium. This was mirrored by a strong increase of ammonia‐oxidizing Thaumarchaeota towards the hypolimnion (13%–21% of bacterioplankton) throughout spring to autumn as revealed by amplicon sequencing and quantitative polymerase chain reaction. Ammonia‐oxidizing bacteria were typically two orders of magnitude less abundant and completely ammonia‐oxidizing (comammox) bacteria were not detected. Both, 16S rRNA gene and amoA (encoding ammonia monooxygenase subunit B) analyses identified only one major species‐level operational taxonomic unit (OTU) of Thaumarchaeota (99% of all ammonia oxidizers in the hypolimnion), which was affiliated to Nitrosopumilus spp. The relative abundance distribution of the single Thaumarchaeon strongly correlated to an equally abundant Chloroflexi clade CL500‐11 OTU and a Nitrospira OTU that was one order of magnitude less abundant. The latter dominated among recognized nitrite oxidizers. This extremely low diversity of nitrifiers shows how vulnerable the ecosystem process of nitrification may be in Lake Constance as Central Europe's third largest lake.

Ammonia‐oxidising archaea living at low pH: Insights from comparative genomics - Craig W. Herbold; Laura E. Lehtovirta‐Morley; Man‐Young Jung; Nico Jehmlich; Bela Hausmann; Ping Han; Alexander Loy; Michael Pester; Luis A. Sayavedra‐Soto; Sung‐Keun Rhee; James I. Prosser; Graeme W. Nicol; et al. (Environmental Microbiology, 2017)
Summary Obligate acidophilic members of the thaumarchaeotal genus Candidatus Nitrosotalea play an important role in nitrification in acidic soils, but their evolutionary and physiological adaptations to acidic environments are still poorly understood, with only a single member of this genus ( Ca . N. devanaterra) having its genome sequenced. In this study, we sequenced the genomes of two additional cultured Ca . Nitrosotalea strains, extracted an almost complete Ca . Nitrosotalea metagenome‐assembled genome from an acidic fen, and performed comparative genomics of the four Ca . Nitrosotalea genomes with 19 other archaeal ammonia oxidiser genomes. Average nucleotide and amino acid identities revealed that the four Ca . Nitrosotalea strains represent separate species within the genus. The four Ca . Nitrosotalea genomes contained a core set of 103 orthologous gene families absent from all other ammonia‐oxidizing archaea and, for most of these gene families, expression could be demonstrated in laboratory culture or the environment via proteomic or metatranscriptomic analyses respectively. Phylogenetic analyses indicated that four of these core gene families were acquired by the Ca . Nitrosotalea common ancestor via horizontal gene transfer from acidophilic representatives of Euryarchaeota. We hypothesize that gene exchange with these acidophiles contributed to the competitive success of the Ca . Nitrosotalea lineage in acidic environments.

Diversity analysis of sulfite‐ and sulfate‐reducing microorganisms by multiplex dsrA and dsrB amplicon sequencing using new primers and mock community‐optimized bioinformatics - Claus Pelikan; Craig W. Herbold; Bela Hausmann; Albert L. Müller; Michael Pester; Alexander Loy (Environmental Microbiology, 2016)
Summary Genes encoding dissimilatory sulfite reductase ( DsrAB ) are commonly used as diagnostic markers in ecological studies of sulfite‐ and sulfate‐reducing microorganisms. Here, we developed new high‐coverage primer sets for generation of reductive bacterial‐type dsrA and dsrB polymerase chain reaction ( PCR ) products for highly parallel amplicon sequencing and a bioinformatics workflow for processing and taxonomic classification of short dsrA and dsrB reads. We employed two diverse mock communities that consisted of 45 or 90 known dsrAB sequences derived from environmental clones to precisely evaluate the performance of individual steps of our amplicon sequencing approach on the Illumina MiSeq platform. Although PCR cycle number, gene‐specific primer mismatches and stringent filtering for high‐quality sequences had notable effects on the observed dsrA and dsrB community structures, recovery of most mock community sequences was generally proportional to their relative input abundances. Successful dsrA and dsrB diversity analysis in selected environmental samples further proved that the multiplex amplicon sequencing approach is adequate for monitoring spatial distribution and temporal abundance dynamics of dsrAB ‐containing microorganisms. Although tested for reductive bacterial‐type dsrAB , this method is readily applicable for oxidative‐type dsrAB of sulfur‐oxidizing bacteria and also provides guidance for processing short amplicon reads of other functional genes.

NxrB encoding the beta subunit of nitrite oxidoreductase as functional and phylogenetic marker for nitrite‐oxidizing N itrospira - Michael Pester; Frank Maixner; David Berry; Thomas Rattei; Hanna Koch; Sebastian Lücker; Boris Nowka; Andreas Richter; Eva Spieck; Elena Lebedeva; Alexander Loy; Michael Wagner; et al. (Environmental Microbiology, 2014)
Summary N itrospira are the most widespread and diverse known nitrite‐oxidizing bacteria and key nitrifiers in natural and engineered ecosystems. Nevertheless, their ecophysiology and environmental distribution are understudied because of the recalcitrance of N itrospira to cultivation and the lack of a molecular functional marker, which would allow the detection of N itrospira in the environment. Here we introduce nxrB , the gene encoding subunit beta of nitrite oxidoreductase, as a functional and phylogenetic marker for N itrospira . Phylogenetic trees based on nxrB of N itrospira were largely congruent to 16 S ribosomal RNA ‐based phylogenies. By using new nxrB ‐selective polymerase chain reaction primers, we obtained almost full‐length nxrB sequences from N itrospira cultures, two activated sludge samples, and several geographically and climatically distinct soils. Amplicon pyrosequencing of nxrB fragments from 16 soils revealed a previously unrecognized diversity of terrestrial N itrospira with 1801 detected species‐level operational taxonomic units ( OTUs ) (using an inferred species threshold of 95% nxrB identity). Richness estimates ranged from 10 to 946 coexisting N itrospira species per soil. Comparison with an archaeal amoA dataset obtained from the same soils [ E nviron. M icrobiol. 14: 525–539 (2012)] uncovered that ammonia‐oxidizing archaea and N itrospira communities were highly correlated across the soil samples, possibly indicating shared habitat preferences or specific biological interactions among members of these nitrifier groups.

amoA ‐based consensus phylogeny of ammonia‐oxidizing archaea and deep sequencing of amoA genes from soils of four different geographic regions - Michael Pester; Thomas Rattei; Stefan Flechl; Alexander Gröngröft; Andreas Richter; Jörg Overmann; Barbara Reinhold‐Hurek; Alexander Loy; Michael Wagner (Environmental Microbiology, 2012)
Summary Ammonia‐oxidizing archaea (AOA) play an important role in nitrification and many studies exploit their amoA genes as marker for their diversity and abundance. We present an archaeal amoA consensus phylogeny based on all publicly available sequences (status June 2010) and provide evidence for the diversification of AOA into four previously recognized clusters and one newly identified major cluster. These clusters, for which we suggest a new nomenclature, harboured 83 AOA species‐level OTU (using an inferred species threshold of 85% amoA identity). 454 pyrosequencing of amoA amplicons from 16 soils sampled in Austria, Costa Rica, Greenland and Namibia revealed that only 2% of retrieved sequences had no database representative on the species‐level and represented 30–37 additional species‐level OTUs. With the exception of an acidic soil from which mostly amoA amplicons of the Nitrosotalea cluster were retrieved, all soils were dominated by amoA amplicons from the Nitrososphaera cluster (also called group I.1b), indicating that the previously reported AOA from the Nitrosopumilus cluster (also called group I.1a) are absent or represent minor populations in soils. AOA richness estimates on the species level ranged from 8–83 co‐existing AOAs per soil. Presence/absence of amoA OTUs (97% identity level) correlated with geographic location, indicating that besides contemporary environmental conditions also dispersal limitation across different continents and/or historical environmental conditions might influence AOA biogeography in soils.

Expression profiles of fhs (FTHFS) genes support the hypothesis that spirochaetes dominate reductive acetogenesis in the hindgut of lower termites - Michael Pester; Andreas Brune (Environmental Microbiology, 2006)
Summary Reductive acetogenesis is an important metabolic process in the hindgut of wood‐feeding termites. We analysed diversity and expression profiles of the bacterial fhs gene, a marker gene encoding a key enzyme of reductive acetogenesis, formyl tetrahydrofolate synthetase (FTHFS), to identify the active homoacetogenic populations in representatives of three different termite families. Clone libraries of polymerase chain reaction‐amplified fhs genes from hindgut contents of Reticulitermes santonensis (Rhinotermitidae) and Cryptotermes secundus (Kalotermitidae) were compared with previously published fhs gene sequences obtained from Zootermopsis nevadensis (Termopsidae). Most of the clones clustered among the ‘Termite Treponemes’, which comprise also the fhs genes of the two strains of the homoacetogenic spirochaete Treponema primitia . The high abundance of treponemal fhs genes in all clone libraries was in agreement with the results of DNA‐based terminal‐restriction fragment length polymorphism (T‐RFLP) analysis. Moreover, in mRNA‐based T‐RFLP profiles of the three termites, only expression of fhs genes of ‘Termite Treponemes’ was detected, albeit at different levels. In C. secundus , only one of the dominating phylotypes was transcribed, while in R. santonensis , the apparently less abundant fhs genes were the most actively expressed. Our results strongly support the hypothesis that spirochaetes are responsible for reductive acetogenesis in the hindgut of lower, wood‐feeding termites.